New Publications in Forensic Science - Natal'ya V. Fetisenkova; Anna A. Ignat'eva (Теория и практика судебной экспертизы, 2018)
This section presents translated abstracts of selected papers that appeared in the following periodicals: Forensic Science International, volumes 262–264, 266, 269 (2016) and volumes 277– 279 (2017), Elsevier Ireland Ltd. (Netherlands) [journal homepage: www.elsevier.com/locate/forsciint] and Journal of the American Society of Questioned Document Examiners, volume 19, number 2 (2016), American Society of Questioned Document Examiners Inc. (USA), [contents lists available online at: www.asqde.org/journal/journal.html].